'Total cost of ownership' of scholarly communication: managing subscription and APC payments together. Issue 1 (1st January 2015) - LAWSON, Stuart
ABSTRACT: Managing subscription journals and open access charges together has created challenges which may in part be dealt with by offsetting the two revenue streams against each other. In order to do this, it is necessary to have reliable financial data about the extent of the two interacting markets. Jisc Collections has been undertaking data collection regarding universities' article publication charge (APC) expenditure. This process is difficult without a standardized way of recording data, so Jisc Collections has developed a standard data collection template and is helping institutions to release data openly. If available data become more comprehensive and transparent, then all parties (libraries, publishers, research funders, and intermediaries) will have better knowledge of the APC market and can more accurately predict the effects of offsetting.